2002
DOI: 10.1111/j.1527-3466.2002.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

LDL Apheresis: An Effective and Safe Treatment for Refractory Hypercholesterolemia

Abstract: Through the efforts of Edward H. Ahrens, LDL apheresis became available for the treatment of patients, often with familial hypercholesterolemia, who have no alternative therapy for severely elevated LDL cholesterol levels. In the U.S., the FDA has approved this treatment for individuals on maximum diet and drugs with an LDL cholesterol greater than 300 mg/dL or greater than 200 mg/dL with coronary artery disease. Unlike plasmapheresis, apolipoprotein B-containing lipoproteins (LDL, Lp(a), and VLDL) are selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We underline the fact that our patient already had a right coronary artery stenosis at the time of liver transplantation. A LDL apheresis procedure can transiently reduce LDL cholesterol levels by more than 50% (17) and may delay the onset of atherosclerosis (18). Nevertheless, it must be frequently repeated (every one to two wk) and is both costly and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…We underline the fact that our patient already had a right coronary artery stenosis at the time of liver transplantation. A LDL apheresis procedure can transiently reduce LDL cholesterol levels by more than 50% (17) and may delay the onset of atherosclerosis (18). Nevertheless, it must be frequently repeated (every one to two wk) and is both costly and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of ezetimibe to statin treatment may result in an additional 20% LDL-C reduction 7 . Apheresis treatment may acutely lower LDL-C level by 70–80% and result in a time-average reduction by 40–50% when performed regularly 24 . Recently a phase 3 randomized placebo control study assessing the efficacy of an anti-apoB ASO, mipomersen, showed a reduction LDL-C of approximately 25% in HoFH treated with maximal tolerated lipid-lowering drug therapy 13 .…”
Section: Panel - Research In Contextmentioning
confidence: 99%
“…However, lipoprotein apheresis is invasive, time consuming, and not readily available for many patients. 4, 5 …”
Section: Introductionmentioning
confidence: 99%